Effect of Extracorporeal Shock Wave Therapy on Different Types of Lumbar Disc Herniation - XIANG Ganggang; CHEN Jiankun; LI Taiyou; XU Shuai; GAO Qilong (康复学报)
ObjectiveTo explore the effect of extracorporeal shock wave (ESW) therapy on different types of lumbar disc herniation (LDH).MethodsA total of 3,454 patients with LDH admitted to the Department of Orthopedics and Traumatology of the Third Affiliated Hospital of Yunnan University of Traditional Chinese Medicine, the First Affiliated Hospital of Yunnan University of Traditional Chinese Medicine, Qujing Hospital of Traditional Chinese Medicine, Xuanhan County People's Hospital from February 2020 to February 2023 were selected. According to the different types of LDH, the patients were divided into the central disc herniation group (1,231 cases), the paracentral disc herniation group (1,081 cases) and the lateral disc herniation group (1,142 cases). All patients received ESW therapy and functional exercise guidance. The visual analogue scale (VAS) and Japanese Orthopaedic Association (JOA) scores were compared among the three groups before treatment, on the 2nd and 6th day of treatment, and at the end of treatment. The inflammatory markers (IL-6, TNF-α) were evaluated before and after treatment, and the intervention effects of ESW in the three groups were comprehensively evaluated.ResultsThere was no significant difference in gender, age, course of disease and stage among the three groups (P>0.05). The VAS score of the three groups after 2 and 6 days of treatment and at the end of the treatment period were all significantly lower than those before treatment (P<0.05). After 2 days of treatment, the central disc herniation group had significantly lower score than the paracentral disc herniation group and the lateral disc herniation group, and the differences were statistically significant P<0.05). However, there was no significant difference among the three groups after 6 days of treatment and at the end of the treatment period (P>0.05). In terms of JOA score, all the three groups showed a significantly higher score after 2 days, 6 days, and at the end of the treatment period, than those before treatment and the differences were statistically significant (P<0.05). After 2 days of treatment, the central disc herniation group had significantly higher score than the paracentral disc herniation group and the lateral disc herniation group, and the differences were statistically significant (P<0.05). There was no significant differences among the three groups after 6 days of treatment and at the end of treatment period (P>0.05). In terms of inflammatory markers (IL-6, TNF-α), the level of IL-6 and TNF-α in the three groups after treatment were significantly lower than those before treatment, and the differences were statistically significant (P<0.05); after treatment, the level of IL-6 and TNF-α in the central disc herniation group were significantly lower than those in the paracentral disc herniation group and the lateral disc herniation group, and the differences was statistically significant (P<0.05).ConclusionESW therapy can relieve pain, restore lumbar function and reduce inflammatory markers in three types of LDH, which are central disc herniation type, paracentral disc herniation type and lateral disc herniation type. It has the most remarkable effect for central LDH. In clinical work, ESW therapy is recommended as a priority for central LDH.